The influence of perceived environmental friendly-office program regulation and public service motivation on pro-environmental behavior of civil servants with OCBE as intervening variable - Bayu Nugroho; Widhy Setyowati; Taufiq Andre Setiyono (Universitas Hayam Wuruk Perbanas, 2021)
Environmental problems such as air pollution, global warming and water scarcity pose a threat to environmental sustainability. One of the causes is the administration of public services. To reduce environmental damage, public organizations must support the implementation of activities that are more environmentally friendly and their employees must display pro-environmental behavior. The research was expected to contribute practical ideas in the form of optimal implementation of environmentally friendly office programs, and theoretical contributions because there were still few researches on pro-environmental behavior of public employees. The study examined the influence of Perceptions of Regulations on the Implementation of Environmentally Friendly Office Programs and Public Service Motivation on the Pro-Environmental Behavior of Civil Servants through Organization Citizenship Behavior Toward Environment (OCBE) as Intervening Variables. The research sample was West Semarang KPP Pratama employees who had implemented an environmentally friendly program. The theoretical basis was TPB (Theory of Planned Behavior) which had been widely used to test pro-environmental behavior. The results showed that the perception of regulation had no significant effect on pro-environmental behavior. Meanwhile, Public Service Motivation and OCBE had a significant influence. Then OCBE mediated the perception of regulation with pro-environmental behavior fully, and public service motivation partially mediated pro-environmental behavior partially.